The Endowment Effect in Games - Michalis Drouvelis; Joep Sonnemans (Tinbergen Institute, 2015)
We study experimentally whether the endowment effect survives in a social and strategic context. Participants are asked for their Willingness-to-Accept (WTA) or Willingness-to-Pay (WTP) to play a series of 2x2 games. In the second part of the experiment, we study the endowment effect in lotteries with the same payoffs as the games in the first part. Our findings provide robust evidence for the endowment effect both in games and in lotteries, with the size of the effect actually being larger in games than in lotteries. We also find that the endowment effect can partly be attributed to optimism.
Keywords: C91; D03; D81; 330; Experiment; Endowment Effect; 2x2 Games